The Mechanobiology and Mechanophysiology of Military-Related Injuries - Gefen, Amit.; Epstein, Yoram; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a state-of-the-art update, as well as perspectives on future directions of research and clinical applications in the implementation of biomechanical and biophysical experimental, theoretical and computational models which are relevant to military medicine. Such experimental and modeling efforts are helpful, on the one hand, in understanding the aetiology, pathophysiology and dynamics of injury development and on the other hand in guiding the development of better equipment and protective gear or devices that should ultimately reduce the prevalence and incidence of injuries or lessen their hazardous effects. The book is useful for military-oriented biomedical engineers and medical physicists, as well as for military physiologists and other medical specialists who are interested in the science and technology implemented in modern investigations of military related injuries.
The Mechanophysiololgy of Stress Fractures in Military Recruits -- Traumatic Brain Injury in the Military: Biomechanics and Finite Element Modelling -- Modeling Skeletal Injuries in Military Scenarios -- Biomechanics of Eye Injury in the Military -- The Biomechanical Basis for Increased Risk of Overuse Musculoskeletal Injuries in Female Soldiers.
Keywords: Biomedical engineering; Surgery; Human physiology; Mechanics, Applied; Solids; Biomaterials; Biomedical Engineering and Bioengineering; General Surgery; Human Physiology; Solid Mechanics; Biomaterials